2017
DOI: 10.1071/rdv29n1ab206
|View full text |Cite
|
Sign up to set email alerts
|

206 CRISPR/Cas9-MEDIATED REPAIR OF THE NHLRC2 LOCUS IN BEEF CATTLE

Abstract: In cattle, a mutation in the NHL-repeat containing 2 genes causes a heritable abnormality referred to as developmental duplications. Calves homozygous for this mutation are affected with a broad range of phenotypes resulting from abnormal neural crest cell migration, most commonly manifested as polymelia, the presence of additional limbs. This mutation has become highly prevalent in Angus beef cattle, as lines of cattle with high genetic merit have been shown to have an increased allele frequency of the mutati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…Our studies have shown that Nhlrc2 knockout (KO) mouse embryos die during gastrulation, indicating an essential role for the protein in embryonic development ( Hiltunen et al, 2022 ). This gastrulation or early neurulation defect is consistent with the anatomic malformations called development duplications (DD, OMIA 002103-9913) 1 that have been observed in association with the NHLRC2 variant p.Val311Ala in Angus cattle, highlighting its function in the development of the central nervous system ( Polkoff et al, 2017 ). Our previous findings from the compound heterozygote FINCA knockin and Nhlrc2 KO mouse model associated hnRNP C2 and RNA metabolism with the FINCA disease pathology, suggesting that NHLRC2 plays an important role in the hippocampus ( Hiltunen et al, 2020 ).…”
Section: Introductionsupporting
confidence: 79%
“…Our studies have shown that Nhlrc2 knockout (KO) mouse embryos die during gastrulation, indicating an essential role for the protein in embryonic development ( Hiltunen et al, 2022 ). This gastrulation or early neurulation defect is consistent with the anatomic malformations called development duplications (DD, OMIA 002103-9913) 1 that have been observed in association with the NHLRC2 variant p.Val311Ala in Angus cattle, highlighting its function in the development of the central nervous system ( Polkoff et al, 2017 ). Our previous findings from the compound heterozygote FINCA knockin and Nhlrc2 KO mouse model associated hnRNP C2 and RNA metabolism with the FINCA disease pathology, suggesting that NHLRC2 plays an important role in the hippocampus ( Hiltunen et al, 2020 ).…”
Section: Introductionsupporting
confidence: 79%
“…With the exception of the mammalian and plant homologs we were unable to find reports on functional studies on these proteins. The mammalian protein is essential, its silencing results in embryonic lethality in mice and mutation of NHLRC2 has been associated with severe disease states [ 2 , 7 ], but is of unknown function.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to having an apparent role in early development, NHLRC2 has been suggested to be a novel serum biomarker for Alzheimer´s disease [ 5 ] and as having an as yet unresolved role in the regulation of ROS-induced apoptosis [ 1 ]. Homozygous deletion of the NHLRC2 gene leads to an embryonic lethality in mice [ 2 , 6 ] and a recently reported mutation in a conserved region of the β-propeller domain NHLRC2 was shown to cause neural tube defects in Angus cattle [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Polkoff et al 25 reported that a mutation in a highly conserved protein-coding region of the NHLRC2 gene in cattle is related to embryonic malformation. Furthermore, homozygous deletion of the NHLRC2 gene in mice yielded an embryonic lethality 39 .…”
Section: Discussionmentioning
confidence: 99%
“…The NHLRC2 gene has been found in many species, from flies to humans, and their sequences are highly conserved during evolution. A recent study reported that a mutation in the NHLRC2 gene in cattle was related to embryonic malformation 25 , suggesting an important role in embryonic development. Based on the amino acid sequence, NHLRC2 is expected to be involved in the regulation of redox states of particular proteins.…”
Section: Introductionmentioning
confidence: 99%